Gender Equality and Sexuality Education in Elementary Schools: Conceptualizing a Smart and Inclusive Learning Framework - Holy Ichda Wahyuni; Endah Hendarwati (International Journal of Elementary Education, 2025)
Sex education in elementary schools is still perceived as a taboo topic and, therefore, has not been systematically integrated into the curriculum and instructional materials. This condition potentially creates gaps in students’ understanding of bodily autonomy, social relationships, and self protection from sexual violence. This study aims to analyze the implementation of sex education in elementary schools and to explore the need for developing supplementary learning media to address the limitations of existing textbook content.This research employed a descriptive qualitative method with a case study design. The research subjects consisted of teachers and school principals. Data were collected through semi-structured interviews and content analysis of Natural and Social Sciences (IPAS) textbooks. The research instruments included an interview guide and a document analysis checklist. Data were analyzed using thematic analysis for interview data and content analysis for documents through coding, categorization, and meaning interpretation stages. The findings indicate that sex education is generally delivered indirectly and primarily focuses on reproductive health, while topics related to body privacy, gender equality, and child protection remain limited in textbooks. These findings highlight the urgency of developing a smart book as a contextual, interactive supplementary learning medium aligned with children’s developmental stages. The implications emphasize the importance of integrating sex education and developing learning media to strengthen child protection.